DIVERSITY OF FRUIT FLIES (TEPHRITIDAE: BACTROCERA SPP.) IN CAMPUS C OF AIRLANGGA UNIVERSITY, SURABAYA, INDONESIA - Sari, Eka Kartika Arum Puspita; Affandi, Moch.; Hariyanto, Sucipto (Treubia, 2025)
This research aims to get information about the species of host plants and fruit flies, composition and structure of community, distribution pattern, and impact of environmental factors to fruit flies in Campus C, Airlangga University. Research was conducted from August to November 2019. A modification of Steiner trap with methyl eugenol 1.5 ml bait was installed in nine sites. Each Steiner trap was placed on a mango tree 1-2 meters above ground level. Trapped fruit fly specimens were collected after one week. Four replications were made, with intervals between two periods of installation. As many as 682 host plants of the fruit flies were found at the study site consisting of 25 species from 15 families. Results showed that 1121 individuals of Bactrocera fruit flies were found, consisting of 5 species, namely B. carambolae, B. dorsalis, B. minuscula, B. occipitalis, and B. musae. The most abundant species was B. carambolae (62.8%), followed by B. dorsalis (27.3%), B. minuscula (8.4%), B. occipitalis (1%), and the lowest was B. musae (0.5%). B. occipitalis has an even distribution pattern, while four other species have aggregated distribution patterns. The diversity index at nine locations ranged from 0.772 (low) to 1.151 (moderate). B. occipitalis has an even distribution pattern, while five other species have aggregated distribution patterns. The diversity index at nine locations ranged from 0.855 (low) to 1.328 (moderate). B. carambolae and B. dorsalis were the dominant species. The presence of fruit flies was influenced by environmental (humidity, temperature, sunlight intensity, wind) and host plant factors.